Magnesium depletion score is a risk factor for all-cause, cancer and cardiovascular disease mortality in cancer survivors: evidence from two prospective cohort studies - Ma, Yunmiao; Li, Minjie; Liu, Xing (Frontiers in Nutrition, 2025)
BackgroundCancer survivors face significant mortality risks, including from cardiovascular disease (CVD) and cancer. Magnesium depletion score (MDS) is a prognostic biomarker, but its prognostic value in cancer survivors is unknown.MethodsThis prospective study utilizes data from two distinct cohorts: the National Health and Nutrition Examination Survey (NHANES) and the Shaanxi Provincial People’s Hospital. We analyzed 3,528 cancer survivors from NHANES (1999–2018) and 473 patients from the hospital cohort. Associations between MDS (0, 1, 2, ≥3) and all-cause, cancer-specific, and CVD mortality were assessed using weighted multivariate Cox regression, Kaplan–Meier analysis and Fine-Gray competing risk model. Predictive accuracy was evaluated using time-dependent ROC curves.ResultsDuring follow-up (median 165 months for NHANES), higher MDS (≥3) was significantly associated with increased mortality risk after full adjustment: all-cause (HR = 2.48, 95% CI: 1.86–3.29), cancer (HR = 2.17, 95% CI: 1.44–3.26), and CVD (HR = 3.89, 95% CI: 1.91–7.91) compared to MDS = 0 (all p for trend<0.001). Kaplan–Meier curves and competing risk model confirmed worse survival with higher MDS. Time-dependent ROC demonstrated good predictive accuracy for all mortality risk. Results remained robust in sensitivity analyses and the single-center cohort.ConclusionHigher MDS is a strong, independent predictor of increased all-cause, cancer-specific, and CVD mortality risk among cancer survivors. MDS provides valuable prognostic information and could aid in risk stratification for personalized survivorship care.